1976
DOI: 10.1136/jcp.29.12.1097
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Brucella spp to tetracycline and its analogues.

Abstract: SYNOPSIS The sensitivity to eight tetracyclines of 100 strains of brucellae, comprising strains of Brucella abortus, Br. melitensis, and Br. suis, was determined. Demethylchlortetracycline was the most effective against all the groups of brucellae, whereas oxytetracycline and chlortetracycline were the least effective. The mean MIC value for demethylchlortetracycline, doxycycline, lymecycline, and tetracycline was < 1 ,ug/ml. Strains of Br. abortus biotype 2 and Br. suis were the most sensitive strains examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
9
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 7 publications
(8 reference statements)
2
9
0
Order By: Relevance
“…The MIC of streptomycin remained essentially unchanged from that observed by many investigators for the past half century (3,12). Rifampin MIC90s in previous studies were reported to range from 0.02 to 0.10 ,ug/ml, values confirmed again by our findings (8,10,12). In vitro susceptibility to co-trimoxazole was also found to be in the range described previously.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…The MIC of streptomycin remained essentially unchanged from that observed by many investigators for the past half century (3,12). Rifampin MIC90s in previous studies were reported to range from 0.02 to 0.10 ,ug/ml, values confirmed again by our findings (8,10,12). In vitro susceptibility to co-trimoxazole was also found to be in the range described previously.…”
supporting
confidence: 80%
“…Minocycline demonstrated the lowest MIC in our study, a finding that has been repeatedly demonstrated for the various tetracycline compounds (8,10,11). The low MIC, however, was not accompanied by a rapid kill.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…to be susceptible to some of the fluoroquinolones [4,[13][14][15]; this investigation was extended to test 8 different fluoroquinolones which are either commercially available or in the various stages of development. The relapse rate with conventional drugs used against B. melitensis has been reported to range between 5-70% [10][11][12]. Compared to these figures, the fluoroquinolones were found to be extremely effective agents against B. melitensis.…”
mentioning
confidence: 88%
“…Therefore, to be effective, the treatment of acute brucellosis requires drugs that penetrate macrophages. With conventional drugs such as tetracycline, aminoglycosides, or sulfonamides, high relapse rates have been reported (8,13,23). More recently, increasing resistance of Brucella spp.…”
mentioning
confidence: 99%